Pelatihan Pelatih TOEFL ITP untuk Guru di Pondok Pesantren Bumi Shalawat - Lutfi Saksono Saksono; Retno Wulan Dari; Ajeng Dianing Kartika; Karwanto Karwanto; Akbar Kuntardi Setiawan (ABISATYA : Journal of Community Engagement, 2026)
This community engagement program addressed the need to strengthen the capacity of teachers at Pondok Pesantren Bumi Shalawat Sidoarjo to serve as internal TOEFL ITP trainers. The program was conducted from September to October 2025 and involved 15 teachers. It employed a participatory training and mentoring approach through needs analysis, pre-test, workshops on TOEFL ITP sections, item analysis practice, lesson-plan development, microteaching, post-test evaluation, and follow-up planning. The results indicated measurable improvement. Participants’ understanding of TOEFL ITP increased from 75% before the program to 100% after the program, while teaching readiness increased from 35% to 80%. The development of training products, including lesson plans, practice materials, and follow-up plans, also improved by 50%. These results show that the program strengthened teachers’ conceptual understanding, pedagogical readiness, and institutional capacity to initiate an internal TOEFL ITP training program. The novelty of the program lies in its train-the-trainer orientation, which focuses on empowering teachers as local facilitators rather than preparing them merely as test takers. Overall, the program contributed to teacher empowerment and provided a practical foundation for sustainable TOEFL ITP support in Islamic boarding school settings.